Engineering the Nanoscaled Morphologies of Linear DNA Homopolymers. Issue 15 (25th June 2021) - Zheng, Mengxi; Li, Qian; Li, Qian; Paluzzi, Victoria E.; Choi, Jong Hyun; Mao, Chengde
Abstract: Supramolecular polymers have unique characteristics such as self‐healing and easy processing. However, the scope of their structures is limited to mostly either flexible, random coils or rigid, straight chains. By broadening this scope, novel properties, functions, and applications can be explored. Here, DNA is used as a model system to engineer innovative, nanoscaled morphologies of supramolecular polymers. Each polymer chain consists of multiple copies of the same short (38–46 nucleotides long) DNA strand. The component DNA strands first dimerize into homo‐dimers, which then further assemble into long polymer chains. By subtly tuning the design, a range of polymer morphologies are obtained; including straight chains, spirals, and closed rings with finite sizes. Such structures are confirmed by AFM imaging and predicted by molecular coarse simulation. Abstract : DNA serves as a model system to engineer various nanoscale morphologies of supramolecular polymers. By subtly tuning the design, a range of polymer morphologies are obtained; including straight chains, spirals, and closed rings with finite sizes.